Five-level transformerless inverter with reduced voltage stress on components - Venkatesan, Rattan Kumar; Lakshmikanthan, Chitra (Institute of Advanced Engineering and Science, 2024)
Leakage current flow is an important issue of transformerless (TL) inverters due to the absence of galvanic isolation between the source and grid sides in grid-connected solar photovoltaic (PV) systems. This article proposes a five-level (5L) TL direct ground point (DGP) type inverter employing two switched capacitors (SCs). The DGP configuration shares a common ground point for the PV negative terminal with grid neutral, thereby completely suppressing the leakage current. The employed semiconductors endure maximum voltage stress equivalent to the input voltage, while the switched capacitors (SCs) are rated at only half of the input voltage. This significantly reduces both the size and cost of the inverter. In addition, it uses reduced power components and has a lower total standing voltage per unit among the recent same art of topologies. A detailed comparison to show the merits of the proposed inverter is presented. Simulations and experiments were conducted at a 1 kW output power level in stand-alone as well as grid-connected mode to validate the feasibility of the proposed inverter.